Uploading Social Media as Indirect Promotion Strategies in Film Destination Tourism: Re-Enactment of Ada Apa dengan Cinta 2 in Sellie Coffee - Ju Hee Bhin (Gadjah Mada Journal of Tourism Studies, 2019)
This study aims at understanding tourist activities and re-enactment of AADC 2 that can potentially be an indirect promotion strategy of Sellie Coffee. Uploading photography of the reenactment of AADC 2 in social media leads to a sensational indirect promotion strategy that needs to be paid any attention. This study is conducted in Sellie Coffee, located in Jalan Prawirotaman, Yogyakarta, Indonesia. This research employs qualitative approach and all the data is obtained through literature study, observation, and interview. The research results show that Instagram, one of a popular social media, provides a complete communication facility, from tourism branding to usergenerated content photography. Moreover, the activity of uploading photos related to AADC 2 in Sellie Coffee visited by film tourists in social media has become one of indirect promotion strategies.